PENGARUH MEDIA PEMBELAJARAN KARTU HURUF TERHADAP KEMAMPUAN PENGENALAN HURUF KELAS A DI RA PERWANIDA 2 PALEMBANG - Dwi Safitri, Novicha; Febriyanti; Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of letter-recognition skills among young children remains a fundamental challenge in early literacy development, particularly because learning practices in Raudhatul Athfal still rely on conventional approaches that do not fully align with children’s learning characteristics. Letter recognition is an essential component of early literacy that requires engaging and developmentally appropriate learning media. In response to this issue, this study aims to determine the effect of letter-card learning media on students’ letter-recognition abilities. This quantitative research employed a quasi-experimental one-group pretest–posttest design involving all class A students at RA Perwanida 2 Palembang. Data were collected through observation and letter-recognition tests, then analyzed using descriptive statistics and paired sample t-test. The findings show a significant improvement in children’s performance, indicated by an increase in the mean score from 11.48 in the pretest to 17.80 in the posttest, supported by a significance value below 0.05. These results confirm that letter-card media has a significant positive effect on enhancing children’s letter-recognition skills. The study recommends the use of letter-card media as an effective learning tool to support early literacy development in early childhood education.